Synthesis of the Antimicrobial S‐Linked Glycopeptide, Glycocin F. Issue 9 (21st January 2015) - Brimble, Margaret A.; Edwards, Pat J.; Harris, Paul W. R.; Norris, Gillian E.; Patchett, Mark L.; Wright, Tom H.; Yang, Sung‐Hyun; Carley, Sarah E.
Abstract The first total synthesis of glycocin F, a uniquely diglycosylated antimicrobial peptide bearing a rare S‐linked N‐acetylglucosamine (GlcNAc) moiety in addition to an O‐linked GlcNAc, has been accomplished using a native chemical ligation strategy. The synthetic and naturally occurring peptides were compared by HPLC, mass spectrometry, NMR and CD spectroscopy, and their stability towards chymotrypsin digestion and antimicrobial activity were measured. This is the first comprehensive structural and functional comparison of a naturally occurring glycocin with an active synthetic analogue.